The mortality cost of carbon - R. Daniel Bressler (Nature Portfolio, 2021)
Climate change is expected to have impacts on human mortality, e.g. through increases in heat waves. Here, the author proposes a new metric to account for excess deaths from additional CO2 emissions, which allows to assess the mortality impacts of marginal emissions and leads to a substantial increase in the social costs of carbon.